PHYTOTHERAPY FOR ENDOMETRITIS AND SUBSEQUENT CONCEPTION RATE IN REPEAT BREEDING CROSSBRED COWS - RAHI, S; GUPTA, H P; PRASAD, SHIV; BAITHALU, R K (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to study the comparative effect of herbal extract of garlic (crude) andashwagandha (hydro-ethanolic) with antibiotic ciprofloxacin for the treatment of endometritis and repeat breedingcondition in cross bred cows. Sixty four repeat breeding cross bred cows with endometritis were divided into eightgroups and treated with PBS, antibiotic ciprofloxacin Ashwagandha 1/U, garlic 1/U, ashwagandha oral, ashwagandhaoral+ garlic 1/U ashwagandha + garlic 1/U, ashwagandha oral+ 1/U, respectively at estrus. At subsequent estrusafter treatment, majority of cows treated with herbal extracts and antibiotic showed better recovery rate evidencedon the basis of clear mucus discharge, negative reaction to white side test, reduction in bacterial load in cervicalmucus. Better conception rate was observed in ashwagandha + garlic group at par with ciprofloxacin treated groupdue to their synergistic effect in combating infection and good immunomodulatory properties (Mishra et al., 2000)as compared to control, where no animal became pregnant. On the basis of present investigation, it is concludedthat garlic+ ashwagandha extract (Group-G) was found as the most effective treatment among all treated groupsand, thus, can replace conventional antibiotic in future for bacterial endometritis leading to repeat breeding conditionin cross bred cows.
Keywords: Cross bred cows; endometritis; repeat breeder; phytotheraphy